Die Protokolle des Preußischen Staatsministeriums : 1817-1934/38 - Preußen. Staatsministerium; Holtz, Bärbel; Paetau, Rainer, 1951- 1951-; Rathgeber, Christina 1986-; Spenkuch, Hartwin, 1960- 1960-; Zilch, Reinhold 1952- (Acta Borussica / Neue Folge)
Registers of the protocols of the Prussian Staatsministerium, from 1815 to 1934/38.